The effects of working memory training in children revealed by behavioral responses and ERP - Jie Xu; Meiqi Deng; Wenya Nan; Dan Cai (Brain and Behavior, 2021)
Abstract Background Recent studies have examined the effect of computerized cognitive training on working memory (WM), but the behavioral and neural effects were uncertain. Also, few studies have explored WM training effects on children using event‐related potentials. The purpose of our study was to investigate the effects of WM training in children, including the effects on behavioral performance and neurophysiological outcomes. Methods Forty‐four healthy children (mean age = 7.76 years, SD = 0.57 years, 18 females) were assigned to the training and control groups. Over 20 training sessions, the training group participated in the computation‐span and spatial N‐back tasks, whereas the control group joined in normal class activities. They all completed the pre‐ and post‐test evaluation of WM tasks (digit span backwards task and N‐back task). Results The results showed that WM training led to improved performance in the digit span backwards task and 2‐back task of post‐test evaluation, shortened P3a and P3b latencies in nontarget trials during the spatial 1‐back task, shortened P3a latency in target and nontarget trials, as well as increased P3b amplitude and shortened P3b latency in target trials during the spatial 2‐back task. Conclusions These results suggested that WM training might enhance children's behavioral performance on WM tasks and brought about neurophysiological changes. This study gives insights into the potential of WM training effects on children's behavioral performance and neurophysiological outcomes.